Booster Seats and Traffic Fatalities among Children - D. Mark Anderson; Sina Sandholt (Institute for the Study of Labor (IZA), 2016)
In an effort to increase booster seat use among children, the National Highway Traffic Safety Administration is encouraging state legislators to promote stricter booster seat laws, yet there is a paucity of information on booster seat efficacy relative to other forms of restraint. Using data from the Fatality Analysis Reporting System for the period 2008-2014 and the sample selection correction proposed by Levitt and Porter (2001), the current study examines the effectiveness of booster seats relative to child safety seats and adult seat belts. For children 6 to 8 years of age, we find that booster seats are more than twice as effective as child safety seats and over 30 percent more effective than standard seat belts at decreasing the likelihood of fatality in a motor vehicle accident. For children 2 to 5 years of age, all three forms of restraint appear equally effective.
Keywords: I12; I18; 330; booster seats; child safety seats; traffic fatalities